Studi Etnobotani Pemanfaatan Tumbuhan Obat Tradisional oleh Masyarakat Nagari Sijunjung - Andania, Meiridha Mutiara; Yesika, Relin; ferdian, arif (Universitas Andalas, 2024)
Minangkabau is one of the ethnics that uses plants as medicine. In this ethnobotanical study, the aim was to find out the use of plants as medicine by the people of Sijunjung. Data collection was carried out directly by interviewing native people. From the result known that there are about 42 types of plants used by the indigenous people of Sijunjung as medicine. Of the 42 types of plants used, sitawa (Costus speciosus) is the most widely used plant in the treatment of fever. Almost all plants used as medicine are taken orally.